Quiste del hepático común perforado - Perdomo, Roberto; Pereyra Borrelli, César (Cirugía del Uruguay, 1976)
In a rare case of congenia! cyst of the common bile duct there was perforation secondary to lithiasic obstruction of terminal choledocus. This gave rise to biliary peritonitis and bile collected i n an extensive retroperitoneal area. This type of condition is diffi- : Sociedad en 1960. Se trataba de un joven de 22 años cult to recognize and it is important to be informed _about it in order to be a ble to establish diagnosis. There follows a description of its surgical treatment a revision of literature, pointing out its outstanding aspects